Effects of exogenous SLs on growth and physiological characteristics of flue-cured tobacco seedlings under different degrees of drought stress - Wang, Xiao-dong; Zhang, Yi-nan; Wang, Xiao-guo; Zhuang, Ye; Ge, Shao-hua (Frontiers in Plant Science, 2025)
BackgroundDrought stress severely affects global crop yields, reduces water availability, and hinders growth. Strigolactones can alleviate damage caused by various abiotic stresses in plants; however, limited research has been conducted on their ability to enhance drought tolerance in tobacco.MethodsThis study evaluated the drought tolerance of ‘Qin Tobacco 96’ (drought-tolerant) and ‘Yun Tobacco 116’ (moisture-sensitive) before and after the application of gibberellic acid lactone at a concentration of 0.2 mg·L⁻¹ under three drought conditions: mild, moderate, and severe. The primary drought tolerance traits were identified from 29 related indicators, including agronomic traits, photosynthetic efficiency, reactive oxygen metabolism, antioxidant enzyme activities, osmotic regulators, and hormone regulation, using affiliation function, principal component analysis, and cluster analysis to categorize the traits. The degree of drought tolerance enhancement in the two tobacco varieties was evaluated under various treatments.ResultsSpraying exogenous strigolactones reduced the adverse effects of drought stress, particularly in the moisture-sensitive Y116 variety. Under drought stress, chlorophyll content and photosynthetic parameters significantly decreased, whereas strigolactone treatment increased both chlorophyll content and photosynthetic efficiency. Strigolactones reduced the accumulation of reactive oxygen species and malondialdehyde content, enhancing the antioxidant capacity of both varieties. Additionally, strigolactones increased the levels of osmoregulatory substances and activated the production of antioxidant enzymes, thereby enhancing drought tolerance. Furthermore, drought stress disrupted the balance of endogenous hormones, decreasing levels of auxin, gibberellic acid, and ribosylzeatin, while increasing abscisic acid levels. Exogenous strigolactones restored this hormonal balance.ConclusionSixteen traits associated with drought tolerance in tobacco were analyzed using principal component analysis, the traits were classified using cluster analysis, and the magnitude of the D-value was determined by calculating the values of the affiliation function and their respective weights. The results indicated that a concentration of 0.2 mg·L⁻¹ of strigolactones enhanced the drought tolerance of tobacco across different levels of drought stress and promoted the growth and development of flue-cured tobacco. However, the interactions between strigolactones and various hormones under drought stress require further investigation to elucidate the underlying molecular mechanisms. The application methods of strigolactones should be optimized.